Transformasi Pembelajaran dengan Manajemen Kurikulum Merdeka di SMK Negeri 9 Makassar - Yusril, Muh.; Syamsudduha, St.; Mardyawati, Mardyawati; Azisah, St.; Yuspiani, Yuspiani (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose - This research examines the implementation of the Merdeka Curriculum at SMK Negeri 9 Makassar, focusing on planning, organization, execution, and supervision. Using a qualitative approach, data was gathered through interviews, observations, and documentation. Method - The study employs a qualitative and phenomenological method, involving interviews with school leaders, curriculum coordinators, the head of the Fisheries Processing Agribusiness Department, and two teachers. Additionally, observations and document analysis were conducted, and data management followed three stages: data reduction, presentation, and conclusion drawing. Findings - The results indicate that the Merdeka Curriculum planning achieved independence within a year but requires improvement, particularly in school operational plans (KOSP), competency aspects, teaching modules, project-based learning (PJBL) implementation, and P5 projects. Organizing the Merdeka Curriculum using a block approach has been initiated, but subject allocation needs improvement due to a shortage of teaching staff. The implementation offers flexibility in inclusive learning by involving students in projects. Supervision through monitoring and evaluation requires further actions to align with learning objectives.Research Implications - This research discusses limitations in design or methodology influencing result interpretation, addressing constraints on generalizability, practical applications, and the utility of findings. The study emphasizes limitations directly related to research problems, highlighting the need for understanding P5 projects, KOSP development, widespread distribution of teaching modules across departments, and addressing teaching staff shortages. Recommendations include educators designing optimal learning programs and student projects.